Analisa dan Penerapan Model Maintenance Quality Function Deployment (MQFD) untuk Meningkatkan Kualitas Sistem Pemeliharaan Mesin Gilingan (Studi Kasus pada PT.PG.X2 Malang) - B.B, Reinaldo Jr. F.; Santoso, Purnomo Budi; Soenoko, Rudy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Maintenance system is critical because if the maintenance goes well it will be able to guarantee the availability of the mechanical equipment so that the production system will running smoothly. One of the mechanical equipment that most important in the manufacturing especially in the sugar mill is the milling machine. The milling machine should always be in a condition that ready for use. In order to guarantee the availability of the machine, maintenance of a good strategy absolutely must be done. This research used MQFD method whereby this method is an integration between QFD and TPM method. According to Pramod et al., Merging the two methods are expected to improve the quality of maintenance as well as to accommodate the all costumer voices both internal customers and external customers as compared to existing methods of maintenance. The results of this study, it is known that the milling machine maintenance needs to be improved in order to improve the performance of milling machines. As the solution, the steps to be taken are Implementation of routine inspection, Train maintenance staff, Assessing and Improving awareness of the operator and machinist, Utilizing softwares to record and analyze machine components data, Execution Planned Component Replacement and cleaning the machine regularly.Keywords:Maintenance Quality Function Deployment (MQFD), Total Productive Maintenance (TPM), House of Quality (HOQ), Quality Function Deployment (QFD)